Decrease in abundance of apurinic/apyrimidinic endonuclease causes failure of base excision repair in culture-adapted human embryonic stem cells - Krutá, Miriama; Bálek, Lukáš; Hejnová, Renata; Dobšáková, Zuzana; Eiselleová, Livia; Matulka, Kamil; Bárta, Tomáš; Fojtík, Petr; Fajkus, Jiří; Hampl, Aleš; Dvořák, Petr; Rotrekl, Vladimír (Stem cells (Dayton, Ohio), 2013)
The inevitable accumulation of chromosomal abnormalities in human embryonic stem cells (hESCs) during in vitro expansion represents a considerable obstacle for cell replacement therapies. To determine the source of chromosomal abnormalities, we examined hESCs maintained in culture for over 55 months for defects in telomere maintenance and DNA repair. Although prolonged culture affected neither telomerase activity nor nonhomologous end joining, the efficiency of base excision repair (BER) was significantly decreased and correlated with reduced expression of apurinic/apyrimidinic endonuclease 1 (APE1), the major nuclease required for BER. Interestingly, the expression of other BER enzymes was unchanged. Addition of human recombinant APE1 protein to nuclear extracts from late passage hESCs increased BER efficiency to the level typical of early passage hESCs. The link between BER and double-strand breaks (DSB) was demonstrated by decreased DSB release after downregulation of APE1 in early passage hESCs via siRNA. Correspondingly lower APE1 level in late passage hESC resulted in slower and less intensive but long lasting DSB release upon ionizing radiation (IR). Downregulation of APE1 in early passage hESCs also led to approximately 30% decrease in γ-H2AX signaling following IR, similar to that in late passage hESCs. We suggest that downregulation of APE1 significantly contributes to the failure of BER during long-term culture of hESCs, and further that BER failure is one of the factors affecting the genomic instability of hESCs by altering BER-dependent DSB release and cell cycle/checkpoint signaling.
Keywords: oprava DNA; Humans; karyotypizace; imunohistochemie; Karyotyping; embryonální kmenové buňky; buněčné linie; DNA-(Apurinic or Apyrimidinic Site) Lyase; dvouřetězcové zlomy DNA; DNA-lyasa (apurinová nebo apyrimidinová); DNA Repair; Cell Line; DNA Breaks, Double-Stranded; Embryonic Stem Cells; Immunohistochemistry; lidé